Ants - Bix, Cynthia Overbeck; Kuribayashi, Satoshi, 1939-; Kuribayashi, Satoshi, 1939- (Minneapolis : Lerner Pub. Co., 1982)
Describes the characteristics and behavior of ants that build nests for storing food and raising their young, ants that spend most of their time traveling, and ants that invade the nests of other ants.
Adaptation of: Ari no sekai / by Satoshi Kuribayashi.
Includes index.
Keywords: Ants -- Juvenile literature; Ants